About a general property for a class of linear positive operators and applications - Pop, Ovidiu T. (Rev. Anal. Numér. Théor. Approx., 2005)
In this paper we demonstrate a general property for a class of linear positive operators. By particularization, we obtain the convergence and the evaluation for the rate of convergence in term of the first modulus of smoothness for the Bernstein operators, Durrmeyer operators, Kantorovich operators and Bleimann, Butzer and Hahn operators.